GEOMETRIC CONSTRUCTIONS AT MATHEMATICS TEACHER TRAINING - HODANOVA, Jitka (Trends in education, 2015)
Students of study Mathematic teaching for elementary school are going to develop threedimensional imagination and solve constructive topic, which they need for their next job. At university study future teachers solve different types of geometrical topics using positional and metrical attribute of basic flat figure. By solving of practical tasks in technical practice we use design methods. The article describes technical constructions and their using at technical drawing.
Keywords: geometric construction; technical construction; technical drawing.